2016
DOI: 10.1186/s12913-016-1676-z
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the patient-centered medical home and preventive care and healthcare quality for non-elderly adults with mental illness: A surveillance study analysis

Abstract: BackgroundPatient-centered medical homes (PCMHs) may improve outcomes for non-elderly adults with mental illness, but the extent to which PCMHs are associated with preventive care and healthcare quality for this population is largely unknown. Our study addresses this gap by assessing the associations between receipt of care consistent with the PCMH and preventive care and healthcare quality for non-elderly adults with mental illness.MethodsThis surveillance study used self-reported data for 6,908 non-elderly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…A recent systematic review reported that PCMHs reduce cost and utilization of PCPs, but that the evidence is still mixed on the effect of PCMHs toward quality and specialist utilization (Jabbapour et al, 2017). Research on the link between PCMHs and patient experience is more limited, but these models have been linked to higher patient satisfaction (Bowdoin et al, 2016;Kottke et al, 2016;Zulman et al, 2017). The relationship between PCMH and physician experience is not well studied, but one analysis of an organizational intervention emphasizing teamwork and team communication demonstrated a link between the intervention and a greater decrease in burnout and a greater increase in job satisfaction (Linzer et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review reported that PCMHs reduce cost and utilization of PCPs, but that the evidence is still mixed on the effect of PCMHs toward quality and specialist utilization (Jabbapour et al, 2017). Research on the link between PCMHs and patient experience is more limited, but these models have been linked to higher patient satisfaction (Bowdoin et al, 2016;Kottke et al, 2016;Zulman et al, 2017). The relationship between PCMH and physician experience is not well studied, but one analysis of an organizational intervention emphasizing teamwork and team communication demonstrated a link between the intervention and a greater decrease in burnout and a greater increase in job satisfaction (Linzer et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 14 MEPS variables used to assess whether respondents received PCC were selected based on synthesized attributes of PCC, face validity, and similar questions used in previous MEPS published work in operationalizing the PCC. 9 - 11 , 15 - 17 The authors (H.L., L.S., and J.Z.) made initial selections and assignments, and the coauthors (J.A.W., X.K., and M.A.B.)…”
Section: Methodsmentioning
confidence: 99%
“…There are relatively few studies with which to compare our results. One survey found little evidence that PCMHs had an impact on use of recommended preventive care for adults with mental illness (27); however, other studies have found modest shifts in care for Medicaid enrollees in the PCMH with severe behavioral health conditions or general medical and psychiatric comorbidity (28)(29)(30)(31). The clinicalcondition criteria used to select our Medicaid sample were less restrictive than those in studies that found some positive effects, and thus there may be differential impacts on persons with more severe conditions that are masked when effects within a population of mixed medical complexity are examined.…”
Section: Discussionmentioning
confidence: 99%